Combination of Fundamental and Technical Analysis of Shares: Revealing the Profit Potential in the Stock Market of PT. United Tractors, Tbk - Gaffar, Samsu; Uleng Akal, Andi Tenri (Manunggal Halim Jaya, 2022)
This research aims to conduct a comprehensive analysis of PT. United Tractors, Tbk shares using a top-down approach, which includes macroeconomic analysis, industry analysis, and company analysis. Additionally, the study aims to determine the intrinsic value of the shares through the Relative Valuation Techniques method and provide suitable recommendations for investors regarding whether to buy, hold, or sell the company's shares. The macroeconomic analysis revealed fluctuations in indicators such as Gross Domestic Product (GDP), inflation, interest rates, money supply, and exchange rate growth. Meanwhile, the industry analysis identified strong competition among similar companies as the dominant force in the market. The threat of new entrants also poses a challenge, especially when competitors target the same market segment. Additionally, the power of suppliers is higher when the number of suppliers is limited compared to the proportion of buyers. Barriers arise when consumers encounter cheaper substitute products. Moreover, the company analysis showcased varying trends in financial ratios such as RTR, FAT, TATO, CR, QR, DER, DAR, GPM, OPM, NPM, ROA, ROS, ROI, EPS, PSR, PER, and PBVR during the period from 2016 to 2021. Furthermore, it was observed that PT. United Tractors, Tbk tends to undervalue its shares by selling them at prices below the intrinsic value. To this end, the study suggests that when the stock market price is lower than the intrinsic value, the shares are undervalued, prompting investors to consider buying. If the stock market price is equal to the intrinsic value, it is fair-valued, and investors are advised to hold. On the other hand, when the stock market price exceeds the intrinsic value, it is overvalued, and investors should consider selling.